Mergers and acquisitions : the case of Cimpor and InterCement - Andrade, Miguel Luís Machado de Oliveira (2015)
In June of 2012 Camargo Corrêa, the Brazilian Family Group that controlled the Brazilian cement producer InterCement, acquired 61% of the Portuguese cement production leader, Cimpor, with an offer price of 5.5 Euros, allowing Camargo Corrêa to take full control of Cimpor by owning 94% of the company. Cement is an industry characterized by huge production scales and high initial investments, with an enduring trend of consolidation among cement’s biggest international producers, and this deal comes at the tail-end of the 2008 financial crisis, which marked the European macroeconomic environment, particularly the sovereign treasury of the PIGS (Portugal, Ireland, Greece and Spain). According to the model used in this work, Cimpor’s share price at the time of the acquisition announcement is found to be undervalued, with 14.8% upside potential. Moreover, adding the forecasted synergies to the model implies a fair offer price of 6.14 Euros, which results in a 23% premium over Cimpor’s closing price.